2002
DOI: 10.1029/2001je001804
|View full text |Cite
|
Sign up to set email alerts
|

Water ice clouds in the Martian atmosphere: General circulation model experiments with a simple cloud scheme

Abstract: [1] We present the first comprehensive general circulation model study of water ice condensation and cloud formation in the Martian atmosphere. We focus on the effects of condensation in limiting the vertical distribution and transport of water and on the importance of condensation for the generation of the observed Martian water cycle. We do not treat cloud ice radiative effects, ice sedimentation rates are prescribed, and we do not treat interactions between dust and cloud ice. The model generates cloud in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 38 publications
8
109
1
1
Order By: Relevance
“…Some very small clouds were seen between L S = 300 • and L S = 360 • in MY 25, however they were smaller than clouds observed the previous year (Benson et al, 2003); this is most likely an effect of the dust storm. Richardson et al (2002) demonstrated that cloud ice content decreases strongly as a function of increasing dust optical depth. The temperature increase lowers the relative hu- midity, suppressing cloud activity (Pearl et al, 2001).…”
Section: Cloud Area and Interannual Variabilitymentioning
confidence: 97%
“…Some very small clouds were seen between L S = 300 • and L S = 360 • in MY 25, however they were smaller than clouds observed the previous year (Benson et al, 2003); this is most likely an effect of the dust storm. Richardson et al (2002) demonstrated that cloud ice content decreases strongly as a function of increasing dust optical depth. The temperature increase lowers the relative hu- midity, suppressing cloud activity (Pearl et al, 2001).…”
Section: Cloud Area and Interannual Variabilitymentioning
confidence: 97%
“…(f (C, T ) cancels out in the Stokes formula.) We adopt the particle radius r = 2 µm, similar to that in the GCM by Richardson et al (2002). Heterogeneous loss of a species i is α i n i ν i A/4, where ν i is the thermal velocity, α i is the reaction probability, and A is the ice aerosol effective area.…”
Section: Heterogeneous Chemistrymentioning
confidence: 99%
“…The targeting of THEMIS based on MOC imagery was from the outset a calculated gamble: the local times of the parent spacecraft were different (4-6 p.m. vs 2 p.m.) and it was expected that there would be some variation in the location of observable meteorological phenomena with local time [e.g., when and where clouds form as predicted by a GCM (Richardson et al, 2002)]. However, in the absence of observations from which to make targeting predictions for the THEMIS local time, the MOC data provided the best reconnaissance.…”
Section: Atmospheric Campaign Planmentioning
confidence: 99%